(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Post-mortem Interval or Time since death is the time interval between the death of the person and the time of examination of the body by the Forensic Expert. Estimation of post-mortem interval with accuracy has major implications in both civil and criminal cases. The external physical changes occur gradually in a predetermined order which helps to fix the approximate range of post mortem interval but they have a disadvantage of high individual variability like age, sex, height, weight, cause of death, environmental factors etc. This lead to the biochemical analysis of various fluid in the body to detect any changes that happens as gradient in the post-mortem period. In this study, the total count and differential count of cells in the cerebrospinal fluid is estimated and the cytological analysis is done in 39 cases in which the time since death is known.